The Impact of Farm Visits on Farmers’ Satisfaction with Extension: Examining the Dependence on Individual Methods in the Caribbean - Wayne G. Ganpat; Lendel K. Narine; Amy Harder (Journal of International Agricultural and Extension Education, 2017)
This research sought to investigate the dependence on farm visits in selected Caribbean islands, and estimate the impact of such visits on farmers’ satisfaction with extension. The study utilized a causal-comparative design using a convenience sample from six major farming countries in the Eastern Caribbean. Descriptive frequencies, ANOVA, principal factor analysis, and hierarchical OLS regression models were presented. It appears the low use of alternate approaches to disseminate information to eastern Caribbean farmers has led to a dependency on farm visits. This is unsustainable primarily because of its high cost, given the financial constraints of countries. Results indicated that while farmers were fairly satisfied with extension, there was a significant difference in satisfaction based on country of residence, and frequency of farm visits was a significant moderator of satisfaction. Countries’ GDP per capita were consistent with satisfaction levels. Proactive initiatives by extension that focus on alternative education approaches are needed; farmers can be clustered into commodity groups and extension can also make use of the good ICT infrastructure in these countries. Extension can influence farmers’ expectations if it capitalizes on other approaches such as ICTs and group visits. Effective use of alternative lower-cost approaches can result in greater ability to deliver each dimension of quality and match farmers’ expectations. Farm visits have become entrenched as the preferred extension method in the Caribbean. This first-time study, which looks at the issue from an extension and economic perspective, shows the urgent need to revisit the farm visit approach to extension.
Keywords: Caribbean; farm visits; farmer satisfaction; extension; dependence.